THE IMPACT OF ABLATIVE LASER THERAPY ON VARIOUS TYPES OF SKIN AGING - Mamedkhanova, I.A.; Mamedova, G.S.; Ismailova, M.Y.; Rustamzade, S.I. (World of Medicine and Biology, 2024)
The purpose of the study was to evaluate changes in facial skin during the use of an ablative fractional laser depending on the morphotype of ageing. 72 patients with involutive skin changes were involved. Group I included 29 patients with a deformative morphotype, Group II included 20 patients with a finely wrinkled morphotype, and Group III – 23 patients with a mixed morphotype. The ablative fractional photothermolysis procedure was carried out using a CO2 laser. To assess the results visual analogue scale and FACE-Q Satisfaction with Skin were used. After therapy, the total score on the FACE-Q Satisfaction With Skin in Group I increased by 42.5 %, in Group II – increased by 40.7 %, in Group III – increased by 41.7 %. After 6 months in the Group I the percentage of patients with preserved effect was 93.1 %, in Group II – 95 %, in Group III – 95.6 %, after 12 months–86.2 %, 85 % and 87 %, respectively. Thus, fractional laser has high effectiveness in therapy for all types of aging.
Keywords: morphotype of aging; fractional photothermolysis; dermatological scale; wrinkles